HUBUNGAN KADAR ALANINE AMINOTRANSFERASE (ALT) TINGGI TERHADAP HASIL ANTIBODI VIRUS HEPATITIS A PADA PENDERITA DEMAM: RELATIONSHIP BETWEEN HIGH ALANINE AMINOTRANSFERAGE (ALT) LEVELS AND ANTIBODY OF HEPATITIS A VIRUS IN FEVER PATIENTS - Anggraini, Rahayu; Nadatein, Ima; Virlianna, Afvidza Delly (Bali Medika Jurnal, 2019)
Hepatitis A is caused by the Hepatitis A virus (HAV) which is a self limiting disease and provides lifelong immunity. HAV sufferers are characterized by fever, nausea, vomiting, decreased appetite, dark yellow urine, pale stools, and high Alanine Aminotransferase (ALT) results. The purpose of this study was to determine whether there is a relationship between high levels of Alanine Aminotransferase (ALT) and levels of Hepatitis A Virus (HAV) antibodies at the Jemursari Islamic Hospital in Surabaya. This type of research is observational with cross-sectional analytic design. The sampling technique was done by purposive sampling with the inclusion criteria of high ALT levels. The number of research samples as many as 27 respondents who examined IgG HAV and IgM HAV using the Rapid Test IgG and IgM HAV brand V Care. The results of this study showed that there was no significant relationship between high ALT levels and the incidence of Hepatitis A with p = 0.185 (p> 0.05) with the Spearman Correlation test.